The The Influence of Unit Command Leadership and Unit Culture on Soldier Performance Mediated by Soldier Job Satisfaction: (Study in the XIII/Merdeka Military Regional Command Headquarters - Tewal, Bernhard; Nelwan, Olivia S.; Wibowo, Yohanis; Sendow, Greis M; Lengkong, Victor P. K. (Archives of Business Research, 2021)
The objective of this research is to determine the relationship between unit commander leadership style and unit culture on soldier performance through job satisfaction as an intervening variable at XIII/Merdeka Military Regional Command Headquarters. The population of this study was based on managerial & staff positions consisting of 364 soldiers. The samples was 61 soldiers of XIII/Merdeka Military Regional Command Headquarters. This study uses quantitative methods. Primary data were collected used a questionnaire as an instrument to prove the results of the study. By using Smart Partial Least Squares (PLS), the analysis of the collected data reveals and tests hypothesis. The research result showed that commander's leadership style did not significantly affect on soldier performance while unit culture has a positively affect on soldier performance.